Isu Feminisme Dakwah Ustadzah Oki di Media Sosial - Taufiqi, Muhammad Alfan (Mekomda: Media Komunikasi Dakwah, 2023)
Feminism movements often occur between gender equality so that women can get access like men. Gender issues in Indonesia have become one of the topics of interest to this day. The phenomenon of gender equality is considered as something that is contrary to the role and position of women in Islam. In Islam, women have received a position of respect that was not obtained before. Preaching is not only done orally and in writing or face to face only. Preaching through social media Social media is considered to be able to lead to effective communication. Indonesia is the largest social media user in the world. Lecture activities are also preaching and a part of the development of information and communication. Conducting lectures of course there is a goal that must be met. There are many models of discourse analysis that have developed to date, but the discourse analysis model of Sara Mills is considered an analytical model that pays attention to discourse related to feminism. Ustadzah Oki is a female speaker who has great popularity in Indonesia. Basically the lecture delivered by Ustadzah Oki and widely circulated on social media, seeks to show a positive image of women.